027 Effect of inter-hospital transfer in patients undergoing endovascular thrombectomy in the early and late time window. (23rd August 2021) - Edwards, Leon; Blair, Christopher; Cordato, Dennis; Manning, Nathan; Cheung, Andrew; Wenderoth, Jason; Cappelen-Smith, Cecilia
Abstract : Objective: Assess the effect of inter-hospital transfer and treatment time on mortality, reperfusion rates and workflow time metrics in patients undergoing endovascular thrombectomy (EVT) for acute ischaemic stroke (AIS) due to large vessel occlusion (LVO) in the anterior cerebral circulation (ACC). Methods: Analysis of a prospective database of consecutive patients undergoing EVT for LVO presenting between January 2017-December 2018 at a single Australian comprehensive stroke centre (CSC). Patients presented directly or were transferred to the CSC from 21 sites across New South Wales and the Australian Capital Territory. A definition of ≤6 hours or >6 hours of stroke onset to treatment (groin puncture) was used for the early time window (ETW) and late time window (LTW) respectively. Results: 154/213 (72%) patients were inter-hospital transfers.There was no significant difference in baseline characteristics including age, National-Institute-of-Health-Stroke-Scale-score, intravenous thrombolysis administration or procedure time between transferred and direct presenters (all p>0.05). Transferred patients within the ETW had worse 90-day functional outcome (35.6% vs 61.0%, Odds ratio [OR] 0.36, 95% confidence interval [CI] 0.17-0.75), higher mortality (25.3% vs 6.8%, OR 6.57, CI 1.48-29.32) and longer stroke-onset to treatment time (180 vs 245 minutes, p<0.01). In the LTW transferred patients there was no significant difference in 90-day functional outcome, mortality or stroke-onset to treatment compared with the directly presenting patients (all p>0.05). Successful reperfusion rates and sICH were similar between cohorts (all p>0.05) Conclusion: Inter-hospital transfer in the ETW but not LTW is associated with longer stroke-onset to treatment, worse 90-day functional outcome and higher mortality.